Surveillance and expected outcome of acute lymphoblastic leukemia in children and adolescents: An experience from Eastern India - Ashis Mukhopadhyay; Sudeshna Gangopadhyay; Swati Dasgupta; Samrat Paul; Soma Mukhopadhyay; Ujjal Kanti Ray (Indian Journal of Medical and Paediatric Oncology)
Objective: Research in Eastern India especially among children and adolescents for acute lymphoblastic leukemia (ALL) have not been well documented until recently when it was conducted at a cancer institute of tertiary care with primary objectives of examining and correlating different cell surface markers involved with respect to disease surveillance thereby highlighting it as a strong prognostic marker for future diagnosis and treatment. Materials and Methods: A total of 500 consecutively selected ALL patients were diagnosed and treated according to National Cancer Institute protocol (MCP 841) for a period of 24-88 months during this hospital-based study. Results: Of the total, 50.4% had a higher incidence of T-ALL and 47.6% had pro-B, B-cell precursor ALL. Disease free survival and event free survival were remarkably higher in B-ALL adolescent patients as compared to T-ALL, who had significantly lower overall survival ratio. Prevalence of T-ALL was also observed in relapse cases for adolescent patients. Conclusions: We conclude that there is an increased prevalence of T-ALL among adolescents in Eastern India. Immunophenotypic analysis might help in proper evaluation and prediction of treatment outcomes with an increased thrust on studying age-specific incident rates enabling well planned future treatments for improved and better outcome.